5-Lipoxygenase deficiency impairs innate and adaptive immune responses during fungal infection. - Adriana Secatto; Lilian Cataldi Rodrigues; Carlos Henrique Serezani; Simone Gusmão Ramos; Marcelo Dias-Baruffi; Lúcia Helena Faccioli; Alexandra I Medeiros (PLoS ONE, 2012)
5-Lipoxygenase-derived products have been implicated in both the inhibition and promotion of chronic infection. Here, we sought to investigate the roles of endogenous 5-lipoxygenase products and exogenous leukotrienes during Histoplasma capsulatum infection in vivo and in vitro. 5-LO deficiency led to increased lung CFU, decreased nitric oxide production and a deficient primary immune response during active fungal infection. Moreover, H. capsulatum-infected 5-LO(-/-) mice showed an intense influx of neutrophils and an impaired ability to generate and recruit effector T cells to the lung. The fungal susceptibility of 5-LO(-/-) mice correlated with a lower rate of macrophage ingestion of IgG-H. capsulatum relative to WT macrophages. Conversely, exogenous LTB4 and LTC4 restored macrophage phagocytosis in 5-LO deficient mice. Our results demonstrate that leukotrienes are required to control chronic fungal infection by amplifying both the innate and adaptive immune response during histoplasmosis.